An integrated marketing communications campaign for Lead Tutorial Mandaluyong - Buluran, Vhalerie S. (Animo Repository, 2016)
This study and campaign intends to propose an integrated marketing campaign for LEAD Tutorial Center, an after school mentoring service that offers all subject tutorial and project collaboration for grade school, high school and college students and enhancement programs in reading and math for kinder to grade 12 and college students. This research was conducted to understand the current situation of educational support industry in the Philippines, the K to 12 education platform and have an insight about parents perception on tutoring. The study looked into the past, current and projected growth of the industry. The Filipino culture gives importance to education. Research shows that Filipinos correlate educational attainment to better employment and higher income in the work place (Nielsen, 2013). The sense of competition in school and importance of academic excellence as perceived by parents has paved the way for the growth of after school tutorial. The one year campaign starting April 2016 will focus on increasing the level of brand awareness among target market, to encourage conversion among parents, increase in number of enrollees and increase in revenue. It will use below the line advertising and digital advertising. The allotted budget is set at P327,000.